Overdiagnosis and mistreatment of malaria among febrile patients at primary healthcare level in Afghanistan: observational study. (24th July 2012) - Leslie, Toby; Mikhail, Amy; Mayan, Ismail; Anwar, Mohammed; Bakhtash, Sayed; Nader, Mohammed; Chandler, Clare; Whitty, Christopher J M; Rowland, Mark
Abstract : Objective To assess the accuracy of malaria diagnosis and treatment at primary level clinics in Afghanistan. Design Prospective observational study. Setting 22 clinics in two Afghan provinces, one in the north (adjoining Tajikistan) and one in the east (adjoining Pakistan); areas with seasonal transmission of Plasmodium vivax and Plasmodium falciparum . Participants 2357 patients of all ages enrolled if clinicians suspected malaria. Interventions Established (>5 years) microscopy (12 clinics in east Afghanistan), newly established microscopy (five clinics in north Afghanistan), and no laboratory (five clinics in north Afghanistan). All clinics used the national malaria treatment guidelines. Main outcome measures Proportion of patients positive and negative for malaria who received a malaria drug; sensitivity and specificity of clinic based diagnosis; prescriber's response to the result of the clinic slide; and proportion of patients positive and negative for malaria who were prescribed antibiotics. Outcomes were measured against a double read reference blood slide. Results In health centres using clinical diagnosis, although 413 of 414 patients were negative by the reference slide, 412 (99%) received a malaria drug and 47 (11%) received an antibiotic. In clinics using new microscopy, 37% (75/202) of patients who were negative by the reference slide received a malaria drug and 60% (103/202) received an antibiotic. In clinics using established microscopy, 50.8% (645/1269) of patients who were negative by the reference slide received a malaria drug and 27.0% (342/1269) received an antibiotic. Among the patients who tested positive for malaria, 94% (443/472) correctly received a malaria drug but only 1 of 6 cases of falciparum malaria was detected and appropriately treated. The specificity of established and new microscopy was 72.9% and 79.9%, respectively. In response to negative clinic slide results, malaria drugs were prescribed to 270/905 (28.8%) and 32/154 (21%) and antibiotics to 347/930 (37.3%) and 99/154 (64%) patients in established and new microscopy arms, respectively. Nurses were less likely to misprescribe than doctors. Conclusions Despite a much lower incidence of malaria in Afghanistan than in Africa, fever was substantially misdiagnosed as malaria in this south Asian setting. Inaccuracy was attributable to false positive laboratory diagnoses of malaria and the clinicians' disregard of negative slide results. Rare but potentially fatal cases of falciparum malaria were not detected, emphasising the potential role of rapid diagnostic tests. Microscopy increased the proportion of patients treated with antibiotics producing a trade-off between overtreatment with malaria drugs and probable overtreatment with antibiotics.